At last comes love [compact disc, unabridged] - Balogh, Mary (Brilliance Audio, 2009)
Only desperation could bring Duncan Pennethorne, the infamous Earl of Sheringford, back home after the spectacular scandal. Forced to wed in 15 days or be cut off without a penny, Duncan chooses the one woman in London in frantic need of a husband: Margaret, the eldest Huxtable. Margaret is forced to accept the irresistible stranger's offer, but once she discovers who he really is, it's too late.